Comparison between conventional biofilters and biotrickling filters applied to waste bio-drying in terms of atmospheric dispersion and air quality - Schiavon, Marco (Environmental technology, 2016)
Biofiltration has been widely applied to remove odours and volatile organic compounds (VOCs) from industrial off-gas and mechanical-biological waste treatments. However, conventional open biofilters cannot guarantee an efficient dispersion of air pollutants emitted into the atmosphere. The aim of this paper is to compare conventional open biofilters with biotrickling filters (BTFs) in terms of VOC dispersion in the atmosphere and air quality in the vicinity of a hypothetical municipal solid waste bio-drying plant. Simulations of dispersion were carried out regarding two VOCs of interest due to their impact in terms of odours and cancer risk: dimethyl disulphide and benzene, respectively. The use of BTFs, instead of conventional biofilters, led to significant improvements in the odour impact and the cancer risk: when adopting BTFs instead of an open biofilter, the area with an odour concentration > 1 OU m(-3) and a cancer risk > 10(-6) was reduced by 91.6% and 95.2%, respectively. When replacing the biofilter with BTFs, the annual mean concentrations of odorants and benzene decreased by more than 90% in the vicinity of the plant. These improvements are achieved above all because of the higher release height of BTFs and the higher velocity of the outgoing air flow